Production Of Antimicrobial Compounds From A Local Marine Bacterial Isolate, Bacillus Sp. (S1a4) - Lim , Hui Ming (2007)

(untitled)
A total of 160 strains of marine microorganisms were supplied by the Fisheries Research Institute, Penang. They were collected from samples all over the shores of Malaysia. Out of those, 134 were bacterial strains, 9 actinomycetes, 3 fungal and 14 yeast isolates. About 113 isolates were found to produce pigments. Non - pigmented strains (white colonies) were the most commonly found (26%) while the yellow coloured strains followed with a close second (25%), orange pigmented isolates (16%), and the rest were brown, beige, light green, dark blue, red, grey and transparent isolates in a small percentage. Among the marine isolates provided, only 88 isolates were tested for antimicrobial activity. Sejumlah 160 penciian mikroorganisma marin dibekaikan daripada institut Penyelidikan Perikanan, Pulau Pinang. Daripada jumlah tersebut, 134 adalah pencilan bacteria, 9 aktinomiset, 3 kulat, dan 14 yis. Sebanyak 113 pencilan didapati menghasilkan pigmen. Pencilan yang tidak berpigmen (koloni putih) adaiah yang paling banyak ditemui (26%), diikuti rapat dengan pencilan berpigmen kuning(25%), berpigmen jingga (16%), dan terlebihnya adalah perang, beige, hijau muda, biru gelap, merah, kelabu dan lutsinar dalam peratusan yang kecil. Daripada kesemua pencilan marin, hanya 88 pencilan sahaja yang diuji aktiviti antimicrobnya.